2018
DOI: 10.1016/j.nicl.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Regional expression of genes mediating trans-synaptic alpha-synuclein transfer predicts regional atrophy in Parkinson disease

Abstract: Multiple genes have been implicated in Parkinson disease pathogenesis, but the relationship between regional expression of these genes and regional dysfunction across the brain is unknown. We address this question by joint analysis of high resolution magnetic resonance imaging data from the Parkinson's Progression Markers Initiative and regional genetic microarray expression data from the Allen Brain Atlas. Regional brain atrophy and genetic expression was co-registered to a common 86 region brain atlas and ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 46 publications
7
50
0
Order By: Relevance
“…Two cortical regions that showed significant changes between patients and controls, also showed changes between the left and right hemisphere. Our findings are in line with those of a previous study showing that cortical atrophy in Parkinson's disease most prominently affects the lateral occipital cortex, particularly in the left hemisphere (Freeze et al, 2018). The temporal pole showed hypertrophy in patients compared to controls, which was only significant in the right hemisphere.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Two cortical regions that showed significant changes between patients and controls, also showed changes between the left and right hemisphere. Our findings are in line with those of a previous study showing that cortical atrophy in Parkinson's disease most prominently affects the lateral occipital cortex, particularly in the left hemisphere (Freeze et al, 2018). The temporal pole showed hypertrophy in patients compared to controls, which was only significant in the right hemisphere.…”
Section: Discussionsupporting
confidence: 93%
“…The AHBA has been combined with functional MRI data of Parkinson's disease patients and revealed that the regional expression of MAPT, but not SNCA, correlated with the loss of regional connectivity . Using a similar approach, correlations were identified between a cortical atrophy pattern and the regional expression of 17 genes implicated in Parkinson's disease (Freeze et al, 2018). Although both studies used spatial transcriptomics to explore gene expression across the whole brain, they only analyzed the expression of a limited set of genes that are of interest to Parkinson's disease, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial gene expression patterns in the human brain have been studied to unravel the pathogenic mechanisms underlying amyloid-β and tau pathology progression in Alzheimer’s disease, revealing proteins that co-aggregate with amyloid-β and tau, and protein homeostasis components 13,14 . Interestingly, by integrating Allen Human Brain Atlas (AHBA) gene expression data 15 with magnetic resonance imaging of PD patients, the regional expression pattern of MAPT and SNCA was associated with loss of functional connectivity in PD 16 , and regional expression of synaptic transfer genes was related to regional gray matter atrophy in PD 17 . This combined gene-MRI analysis illustrates the importance of local gene expression changes on functional brain networks.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the molecular mechanisms underlying changes in structural and functional networks in PD, imaging data has been integrated with brain wide expression atlases of the healthy brain (Hawrylycz et al 2015; Arnatkevičiūtė et al 2019). Regional brain atrophy in PD patients was found to be correlated with the expression of genes implicated in trans-synaptic alpha-synuclein transfer (Freeze et al 2018) and a loss of regional connectivity in PD patients was correlated with the regional expression of MAPT in the healthy brain (Rittman et al 2016). These studies show that combining imaging data in PD and gene expression from the healthy brain can shed light on the molecular mechanisms underlying the observed differences between PD and controls.…”
Section: Introductionmentioning
confidence: 99%